2003
DOI: 10.1080/07448480309595728
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Overweight, Obesity, Diet, and Physical Activity in College Students

Abstract: The authors surveyed 738 college students aged 18 to 27 years to assess overweight, obesity, dietary habits, and physical activity. They used BMI (body mass index) > or = 25 kg/m2 or BMI > or = 85th percentile and BMI > or = 30 kg/m2 or BMI > or = 95th percentile to estimate overweight and obesity in those aged < or = 19 years. To define overweight and obesity in those > or = 20 years, they used BMI > or = 25 kg/m2 and > or = 30 kg/m2. They found overweight rates of 21.6% using BMI directly and 16.2% using BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
265
7
15

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(309 citation statements)
references
References 19 publications
22
265
7
15
Order By: Relevance
“…Results presented in the current paper are in agreement with other studies reporting unfavourable dietary habits, particularly with regard to the consumption of fruit and vegetables (48) , fat and sugar, dietary fibre (49) and fried/ high-fat fast food (50,51) , among university students from countries in Europe and elsewhere. Attending university brings about increased freedom and independence during which time young people have to learn how to take care of themselves, including from a nutritional point of view.…”
Section: Discussionsupporting
confidence: 92%
“…Results presented in the current paper are in agreement with other studies reporting unfavourable dietary habits, particularly with regard to the consumption of fruit and vegetables (48) , fat and sugar, dietary fibre (49) and fried/ high-fat fast food (50,51) , among university students from countries in Europe and elsewhere. Attending university brings about increased freedom and independence during which time young people have to learn how to take care of themselves, including from a nutritional point of view.…”
Section: Discussionsupporting
confidence: 92%
“…22 Whereas in the United States and United Arab Emirates the prevalence of overweight and obesity were 35% among the college students. 15,23,24 In contrast the prevalence of overweight and obesity among the Iranian male college students were only 7.9 % 25 and it was even low (2.9%) among the Chinese college students. 19 The prevalence rate of obesity in the current study is similar to the studies done by Majeed and Anding et al and it is slightly higher than the study done in Abha by Hakeem et al among the female college students.…”
Section: Discussionmentioning
confidence: 88%
“…8 Sudden transitions from school life to the college life changes the dietary pattern among the college students which causes overweight and obesity. 15 The previous study done by Rasheed et al reported that the prevalence of either overweight or obesity among the female health college students was 30.6 %. Therefore the current study aims at assessing the prevalence of overweight and obesity among the male college students and any association between their body weight and eating habits.…”
Section: Introductionmentioning
confidence: 99%
“…In Libya, a mere 11.2% of students achieved the VPA guidelines (7). One in three university students are sedentary and become less physically active through their college years (8)(9)(10); and whilst university students are generally the more educated segment of the population, college students gain weight at a rate ≈6 times higher than that of the general population (11).…”
Section: Introductionmentioning
confidence: 99%